Atrial septal aneurysm and cryptogenic stroke: an arrhythmic approach to pathophysiology - Ertan Yetkin; Hasan Atmaca; Bilal Cuglan; Kenan Yalta (Hygeia Press di Corridori Marinella, 2023)
The connection between cryptogenic stroke and atrial septal aneurysm (ASA) with or without patent foramen ovale (PFO) has been a debated topic for decades with regard to pathophysiological mechanisms and clinical consequences. Indirect evidences to support the association between cryptogenic stroke and ASA through atrial fibrillation (AF) have been reported sparsely in the literature. Rather than the in-situ thrombus formation in aneurysmatic atrial septal tissue and paradoxical embolization through the PFO, paroxysmal AF-induced development of thrombus in the left or right atrial chamber and subsequent embolization is more likely to be the scenario to explain the cryptogenic stroke in patients with ASA.